Analysis of Ergonomics Risk Factors and Manual Material Handling Assessing Alternative Using Cost Benefit Methods - Eko Nurmianto; Udisubakti Ciptomulyono (Institut Teknologi Sepuluh Nopember, 2014)
This research to analyze the factors that cause risks of low back pain (L5/S1) on Manual Material Handling activities at raw material warehouse and finished goods warehouse. Objective is to determine the factors that cause low back pain (L5/S1), analyze the proposed improvement work system alternative with benefit cost ratio (B/C). The importance of cost-benefits analysis of ergonomics interventions has been emphasized (Tompa et al., 2009; Rivilis et al., 2008). Methodology by observing MMH working system, and distributing job discomfort survey. For the quantitative calculation used RWL, LI and Chaffin’s Model. The model of analysis shows the factor effected to RWL and LI is variable V (vertical distance), D (distance movement), and L (heavy of load). Examples of alternatives proposed : (1) addition of scissor of lift trolleys, (2) addition in amount of workers and (3) modifying of lifting method. Alternative whose the B/C value ≥ 1 are feasible economically to be used. Top management needs a cost-benefit analysis proving the positive outcomes. This economics evaluation showed that ergonomic intervention justifies the costs of the implementation, leading to positive outcomes.